Best Answer

Divide all terms by 2 and it can then be factored to (2x+1)(5x+2)

Q: 20x to the power 2 plus 18x plus 4?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

11x = 20x +1811x-20x=18x(11-20)=18-9x=18x=-2

x4 + 2x3 - 9x2 + 18x = x(x3 + 2x2 - 9x + 18) which I do not think can be factorised further.

20x+7=5x+10 15x=3 3/15=.2 x=.2

x2 + 20x + 4 = 0 x2 + 20x + 100 = 96 (x + 10)2 = 96 x + 10 = ±961/2 x = -10 ±961/2 x = -10 ±4√6

Because: (9-x)(9-x) = 81-18x+x^2

Related questions

11x = 20x +1811x-20x=18x(11-20)=18-9x=18x=-2

x=-1

x2 + 36 = 20x so x2 - 20x + 36 = 0 so x2 - 2x - 18x + 36 = 0 or x(x - 2) - 18(x - 2) = 0 that is (x - 2)(x - 18) = 0 so x - 2 = 0 or x - 18 = 0 ie x = 2 or x = 18

4x2+20x+25 (2x+5)^2

x4 + 2x3 - 9x2 + 18x = x(x3 + 2x2 - 9x + 18) which I do not think can be factorised further.

Combine all lie term: x + x - 22x = -20x 2 + 1 = 3 So the answer is -20x +3 or 3 - 20x

20x+7=5x+10 15x=3 3/15=.2 x=.2

6x2-18x+12 = (6x-6)(x-2)

5x^2 + 20x

x2 + 20x + 4 = 0 x2 + 20x + 100 = 96 (x + 10)2 = 96 x + 10 = ±961/2 x = -10 ±961/2 x = -10 ±4√6

3x3+15x2+18x = 3x(x2+5x+6) = 3x(x+2)(x+3)

2(x + 6)(x + 3)